Optimization of Bioethanol Synthesis from Durian Seeds Using Saccharomyces Cerevisiae in Fermentation Process - Masturi, Masturi; Alighiri, Dante; Dwijananti, Pratiwi; Widodo, Rahmat Doni; Budiyanto, Saraswati Putri; Drastisianti, Apriliana (Universitas Negeri Semarang, 2020)
Bioethanol is an alternative energy of environmentally friendly as a substitute for petroleum. Sucrose, starch, and fibrous cellulose (lignocellulose) are the main ingredients for bioethanol production. The material is very easy and abundant to get from the waste of agricultural crops. One of these agricultural wastes in Indonesia that have not been used optimally is durian seeds. Durian seeds only become waste and are not commercially useful, even though they contain high carbohydrates, which is possible as a potential new source for bioethanol production. In this work, an experimental study was conducted on bioethanol synthesis from durian seeds through fermentation by Saccharomyces cerevisiae yeast in aerobic fermenter. The process for the production of starch-based bioethanol includes milling, hydrolysis, detoxification, fermentation, and distillation. At the stage of fermentation, variations in the duration of fermentation were applied for 1-11 days. Carbohydrates contained in durian seed flour are 11.541%, which is the largest content. The highest result of ethanol content is 14.72 % (v/v) in 9 day fermentation periods by using Saccharomyces cerevisiae in aerobic conditions. Distillation to enrich bioethanol was carried out by batch vacuum distillation at 68°C for ± 180 minutes and produced bioethanol with a purity of 95%.